Positive psychology: the science of well-being - Zelenski, John M. (London : Sage, 2025)
John Zelenski's unique storytelling approach provides a broad and engaging introduction to positive psychology. Strongly guided by empirical work, and reviewing the lessons learned since the founders' original vision of the field, this text encourages you to think critically and to look to the future by exploring positive psychology's potential to inform social change. The second edition has been thoroughly updated to reflect the latest research, with more cross-cultural coverage and a substantial new section on meaning in life and how to find it. It also emphasizes how the science of well-being can be applied to our own lives and to the well-being of entire societies, through'Application' boxes describing how positive psychology is used in the real world and'Try It' exercises giving you the chance to try out theories and practices for yourself! John Zelenski is a Professor of Psychology at Carleton University in Ottawa, Canada'-- Provided by publisher.
Describing the Science of Positive Psychology -- Positive Emotions -- Happiness -- Personality -- The Self -- Thinking -- Social and Physical Environments -- Close Relationships -- Stability and Change -- Looking Forward.
Keywords: Positive psychology